Teloscalpellum antarcticum - Shalaeva, Kate; Boxshall, Geoff (Zenodo, 2014)
Teloscalpellum antarcticum (Hoek, 1883) Fig. 24 Scalpellum antarcticum Hoek, 1883: 95, pl. IV, figs 16–17. Arcoscalpellum antarcticum : Newman & Ross, 1971: 50–51, fig. 17. Teloscalpellum antarcticum : Zevina, 1981a: 377, fig. 293; Young, 2001b: 464, fig. 7. Material examined. Holotype NHM UK 20013.1113, Stn 153: Indian Ocean, Antarctic (off Prince Elizabeth Land); 3065 m. Diagnosis. Only the description of Hoek (1883) is available, but this does not provide details of the appendages. Distrbution. Indian Ocean, Antarctic. Known depth 3065 m. Remarks. The species is represented by a single specimen. It is distinguished by the particular form of the carinal latus that “also may present variations within the limits of a species” (Hoek, 1883). Genus Trianguloscalpellum Zevina, 1978 Arcoscalpellum Hoek, 1907: 85 (part); Pilsbry, 1907a: 47; Newman & Ross, 1971: 42 (part). Trianguloscalpellum Zevina, 1978b: 1349; Liu & Ren, 1985: 205. Diagnosis. Capitulum with 13 or 14 plates; carinal latus triangular, umbo apical inframedian latus triangular or rectangular, umbo apical, reaching upper latus . Type species. Scalpellum balanoides Hoek, 1883. Composition. 25 species. Distribution. Worldwide, excluding Arctic. Known depth range 124 to 6135 m. Remarks. Trianguloscalpellum is diagnosed by the possession of an apical umbo on all of the plates, and comprises two distinct species groups. One group (cited by Pilsbry (1907a) as Scalpellum velutinum (= Arcoscalpellum michelottianum) group) consists of species that attain a large size and have a thick and pilose cuticle. These species appear to be similar to some of the large species of the genera Litoscalpellum and Arcoscalpellum . The other group comprises species of Trianguloscalpellum that are very small and have a thin, often hairless cuticle. They are very different in appearance from the large species. The monophyletic status of this genus should be redefined by molecular analysis. Genus Trianguloscalpellum Zevina, 1978 Arcoscalpellum Hoek, 1907: 85 (part); Pilsbry, 1907a: 47; Newman & Ross, 1971: 42 (part). Trianguloscalpellum Zevina, 1978b: 1349; Liu & Ren, 1985: 205. Diagnosis. Capitulum with 13 or 14 plates; carinal latus triangular, umbo apical inframedian latus triangular or rectangular, umbo apical, reaching upper latus . Type species. Scalpellum balanoides Hoek, 1883. Composition. 25 species. Distribution. Worldwide, excluding Arctic. Known depth range 124 to 6135 m. Remarks. Trianguloscalpellum is diagnosed by the possession of an apical umbo on all of the plates, and comprises two distinct species groups. One group (cited by Pilsbry (1907a) as Scalpellum velutinum (= Arcoscalpellum michelottianum) group) consists of species that attain a large size and have a thick and pilose cuticle. These species appear to be similar to some of the large species of the genera Litoscalpellum and Arcoscalpellum . The other group comprises species of Trianguloscalpellum that are very small and have a thin, often hairless cuticle. They are very different in appearance from the large species. The monophyletic status of this genus should be redefined by molecular analysis. : Published as part of Shalaeva, Kate & Boxshall, Geoff, 2014, An illustrated catalogue of the scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) collected during the HMS " Challenger " expedition and deposited in the Natural History Museum, London, pp. 1-63 in Zootaxa 3804 (1) on pages 37-38, DOI: 10.11646/zootaxa.3804.1.1, http://zenodo.org/record/4917932 : {"references": ["Hoek, P. P. C. (1883) Report on the Cirripedia collected by H. M. S. \" Challenger \" during the years 1873 - 1876. Systematic part. Report on the Scientific Results of the Voyage H. M. S. \" Challenger \", during the years 1873 - 7, Zoology, part 25 (8), 1 - 169.", "Newman, W. A. & Ross A. (1971) Antarctic Cirripedia. Antarctic Research Series, 14. American Geophysical Union, Washington, 257 pp.", "Zevina, G. B. (1981 a) Cirriped crustaceans of the suborder Lepadomorpha (Cirripedia, Thoracica) of the World Ocean. Part 1. Family Scalpellidae. Opredeliteli po Faune SSSR, Leningrad, 398 pp. [in Russian]", "Young, P. S. (2001 b) Redescription of Scalpellopsis striatociliata Broch, 1922, with a discussion on its phylogenetic position and the peduncular plate pattern in scalpellids. Journal of Crustacean Biology, 21 (2), 456 - 468. http: // dx. doi. org / 10.1163 / 20021975 - 99990147", "Hoek, P. P. C. (1907) The Cirripedia of the Siboga expedition A. Cirripedia Pedunculata. Siboga Expeditie Monographe, 31 (a), 1 - 127.", "Pilsbry, H. A. (1907 a) The Barnacles (Cirripedia) contained in the collections of the U. S. National Museum. Bulletin of the United States National Museum, 60, 1 - 122. http: // dx. doi. org / 10.5479 / si. 03629236.60.1", "Zevina, G. B. (1978 b) A new classification of the Scalpellidae (Cirripedia, Thoracica). Part 2 Subfamilies Arcoscalpellinae and Meroscalpellinae. Zoologicheskii Zhurnal, 57 (9), 1343 - 1352. [in Russian]", "Liu, R. & Ren, X. (1985) Studies on Chinese Cirripedia (Crustacea). 6. Suborder Lepadomorpha. Studia Marina Sinica, 10, 179 - 184."]}